2017
DOI: 10.7448/ias.20.4.21591
|View full text |Cite
|
Sign up to set email alerts
|

HIV treatment and care services for adolescents: a situational analysis of 218 facilities in 23 sub‐Saharan African countries

Abstract: Introduction: In 2013, an estimated 2.1 million adolescents (age 10–19 years) were living with HIV globally. The extent to which health facilities provide appropriate treatment and care was unknown. To support understanding of service availability in 2014, Paediatric‐Adolescent Treatment Africa (PATA), a non‐governmental organisation (NGO) supporting a network of health facilities across sub‐Saharan Africa, undertook a facility‐level situational analysis of adolescent HIV treatment and care services in 23 coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 24 publications
5
78
1
Order By: Relevance
“…We observed that lack of training in transitioning ALHIV, lack of clear guidelines or tools to support transition, inadequate human resource and refusal of ALHIV to transition to adult care negatively in uenced successful transition. These ndings were consistent with other ndings that explored provider's perspective on ALHIV transition [25][26][27][28][29][30][31][32][33]. Studies from Uganda and South Africa [31,32] found that training, lack of clear guidelines or tools to support transition and overburdened SPs affected successful transition [28][29][30].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We observed that lack of training in transitioning ALHIV, lack of clear guidelines or tools to support transition, inadequate human resource and refusal of ALHIV to transition to adult care negatively in uenced successful transition. These ndings were consistent with other ndings that explored provider's perspective on ALHIV transition [25][26][27][28][29][30][31][32][33]. Studies from Uganda and South Africa [31,32] found that training, lack of clear guidelines or tools to support transition and overburdened SPs affected successful transition [28][29][30].…”
Section: Discussionsupporting
confidence: 86%
“…Also, all previous studies were from high income countries such as the USA and Canada with stronger health systems than Malawi. Only a few studies have been conducted in Africa , the majority of these have been qualitative focusing on exploring the perception of patients and providers with regard to barriers and facilitators of successful transition [25][26][27][28][29][30][31][32][33]. However, our ndings of poor implementation delity of HIV teen club transition protocol in most health facilities suggest that our ndings on low transition are valid.…”
Section: Discussionmentioning
confidence: 88%
“…Sustaining ART adherence is critical to achieve virological suppression, prevent drug resistance, halt disease progression, and prevent transmission [48,49,89]. Evidence suggests that AYALHIV fail to achieve and maintain adequate adherence.…”
Section: Aya Hiv Care In Low and Middle Income Countriesmentioning
confidence: 99%
“…Available evidence shows that MSM who disclose their orientation, through choice or necessity, report family rejection, public humiliation, harassment by authorities and ridicule by health-care workers (Ayehu et al 2016;Muthengi et al 2016). This population often face significant challenges in accessing HIV care and treatment (Mark et al 2017) due to stigma and discrimination from health providers (Godia et al 2013), and ignorance within health systems (Johnston et al 2017) about their sexual orientation (World Health Organization 2014). Inadequate healthcare providers' skills have been identified as a key barrier to provision of services to key populations (Baggaley et al 2015).…”
Section: Introductionmentioning
confidence: 99%